Worldwide Prevalence and Trends in Unintentional Drug Overdose: A Systematic Review of the Literature - Martins, Silvia S.; Sampson, Laura; Cerdá, Magdalena; Galea, Sandro (American journal of public health (1971), 2015)
Background. Drug overdose is an important, yet an inadequately understood, public health problem. Global attention to unintentional drug overdose has been limited by comparison with the scope of the problem. There has been a substantial increase in drug overdose incidence and prevalence in several countries worldwide over the past decade, contributing to both increased costs and mortality. Objectives. The aim of this study was to systematically synthesize the peer-reviewed literature to document the global epidemiological profile of unintentional drug overdoses and the prevalence, time trends, mortality rates, and correlates of drug overdoses. We searched different combinations of Medical Subject Headings (MeSH) terms in PubMed for articles published from 1980 until July 2013, and we organized these results in tabular spreadsheets and compared them. We restricted the search to English-language articles that deal with unintentional overdose, focusing on 1 or more of the following key constructs: prevalence, time trends, mortality rates, and correlates. The term “overdose” as a MeSH major topic yielded 1076 publications. In addition, we searched the following combinations of nonmajor MeSH terms: “street drugs” and “overdose” yielded 180, “death” and “overdose” yielded 114, and “poisoning” and “drug users” yielded 17. There was some overlap among the searches. Based on the search and inclusion and exclusion criteria, we selected a total of 169 relevant articles for this article based on a close review of abstracts. Results. We found wide variability in lifetime prevalence of experiencing a nonfatal overdose or witnessing an overdose, and in mortality rates attributable to overdose. Lifetime prevalence of witnessed overdose among drug users (n = 17 samples) ranged from 50% to 96%, with a mean of 73.3%, a median of 70%, and a standard deviation of 14.1%. Lifetime prevalence of drug users personally experiencing a nonfatal overdose (n = 27 samples), ranged from 16.6% to 68.0% with a mean of 45.4%, a median of 47%, and a standard deviation of 14.4%. Population-based crude overdose mortality rates (n = 28 samples) ranged from 0.04 to 46.6 per 100 000 person-years. This range is likely attributable to the diversity in regions, time periods, and samples. Most studies on longitudinal trends of overdose death rates or overdose-related hospitalization rates showed increases in overdose death rates and in overdose-related hospitalization rates across time, which have led to peaks in these rates at the present time. An overall trend of increasing deaths from prescription opioid use and decreasing deaths from illicit drug use in the past several years has been noted across most of the literature. With the increase in prescription opioid overdose deaths, drug overdose is not just an urban problem: rural areas have seen an important increase in overdose deaths. Lastly, cocaine, prescription opioids, and heroin are the drugs most commonly associated with unintentional drug overdoses worldwide and the demographic and psychiatric correlates associated with unintentional drug overdoses are similar globally. Conclusions. There is a need to invest in research to understand the distinct determinants of prescription drug overdose worldwide. Several other countries need to collect in a systematic and continuous fashion such data on sales of prescription opioids and other prescription drugs, nonmedical use of prescription drugs, and hospitalization secondary to overdoses on prescription drugs. The sparse evidence on the environmental determinants of overdose suggests a need for research that will inform the types of environmental interventions we can use to prevent drug overdose. Methodological issues for future studies include enhancing data collection methods on unintentional fatal and nonfatal overdoses, and collecting more detailed information on drug use history, source of drug use (for prescription drugs), and demographic and psychiatric history characteristics of the individual who overdosed.